2020
DOI: 10.26444/aaem/124165
|View full text |Cite
|
Sign up to set email alerts
|

The impact of xenoestrogens on effectiveness of treatment for hormone-dependent breast cancer – current state of knowledge and perspectives for research

Abstract: Introduction. Breast cancer is the most common cancer occurring in women and causing the highest number of deaths among them. The role of xenoestrogens has been the subject of many studies in the pathogenesis of breast cancer. Less is known about the impact of xenoestrogens on the effectiveness of hormone therapy used to treat breast cancer, and thus possible drug-xenostrogen interactions. Objective. The aim of this review is to summarize the current state of knowledge and present perspectives for further rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…This may have significance for breast cancer in that S-(-)equol producer status has been linked to lower breast cancer risk [89]; however, further studies are needed to evaluate the bacterial metabolism of soy isoflavones in breast cancer patients whose tumors contain distinct estrogen receptor profiles. In summary, while there are obviously considerable commercial drivers behind the popular usage of dietary soy isoflavones as antioxidants and anti-inflammatory agents, their potential to counteract or modulate endocrine responses remains a concern [90,91].…”
Section: Human Exposure To Environmental Estrogens and Implications F...mentioning
confidence: 99%
“…This may have significance for breast cancer in that S-(-)equol producer status has been linked to lower breast cancer risk [89]; however, further studies are needed to evaluate the bacterial metabolism of soy isoflavones in breast cancer patients whose tumors contain distinct estrogen receptor profiles. In summary, while there are obviously considerable commercial drivers behind the popular usage of dietary soy isoflavones as antioxidants and anti-inflammatory agents, their potential to counteract or modulate endocrine responses remains a concern [90,91].…”
Section: Human Exposure To Environmental Estrogens and Implications F...mentioning
confidence: 99%
“…Furthermore, the majority of breast cancers are hormone-dependent, 21 and hormones could stimulate cancer cell growth by interacting with respective receptors 22 including estrogen receptors, progesterone receptors, glucocorticoid receptors (GR), and androgen receptors. 23,24 Recent research showed that GR was found to be highly expressed in breast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common cancer in women, affecting 2.1 million women worldwide each year and causing the largest number of cancer-related deaths in women [ 1 ]. According to the data providing by American Cancer Society, 13% of women will develop breast cancer in their lifetime, and 3% of them will die from it [ 2 ].…”
Section: Introductionmentioning
confidence: 99%